DIGITAL MATH COMIC DEVELOPMENT BASED ON THINKING TO INCREASE STUDENTS' INTEREST IN LEARNING - Nurhasanah, Nurhasanah; Irvan, Irvan; Doly Nasution, Marah; Sarman Hadi, Nanang (Prima: Jurnal Pendidikan Matematika, 2025)
Digital Math Comic based on the Experience, Interaction, Communication, Reflection (MIKIR) approach is deliberately developed into a learning media needed in mathematics learning activities, especially on the material of Arithmetic Rows and Rows. So the author aims this research to find out the MIKIR-based learning approach that has existed before, the specifications of Digital Math Comic learning media, the feasibility of MIKIR-based Digital Math Comic, the advantages and disadvantages of MIKIR-based Digital Math Comic, and how MIKIR-based Digital Math Comic can increase student interest in learning. This research is a research and development (R&D) method using Thiagarajan's 4-D research model: Define, Design, Develop, and Dessiminate. The subjects of the study were students of grade VIII of SMP Muhammadiyah 1 Medan in the academic year 2023/2024 totalling 71 students. The types of data were qualitative data and quantitative data. The data were analysed qualitatively and quantitatively. The research instruments used were Digital Math Comic assessment sheets by material, language, and media expert lecturers, mathematics teachers, peers, student learning interest tests and student response questionnaires. The method of data collection through questionnaires/questionnaire sheets using a Likert scale. The results of this study indicate that the MIKIR-based Digital Math Comic is empirically proven to be valid, feasible to use, and able to increase students' interest in learning. As shown by the average score given by the validators which is 4.35 has a very good classification. Students' learning interest increased as indicated by the percentage increase in learning interest by 23% from 57% to 80%. Then the students' response to Digital Math Comic got a score of 4.2 with a good classification.